Emigration and wages in source countries : evidence from Mexico - Mishra, Prachi, 1975- (IMF working paper, 2006)
This paper empirically examines the effect on wages in Mexico of Mexican emigration to the United States, using data from the Mexican and United States censuses from 1970-2000. The main result in the paper is that emigration has a strong and positive effect on Mexican wages. There is also evidence for increasing wage inequality in Mexico due to emigration. Simple welfare calculations based on a labor demand-supply framework suggest that the aggregate welfare loss to Mexico due to emigration is small. However, there is a significant distributional impact between labor and other factors.